Changing with the Tide: The Shifting Orientations of Foreign Policies in Sub-Saharan Africa (Nordic Journal of African Studies, 1999)
Foreign policy orientations in sub-Saharan Africa (SSA) are in flux. Since the fullscale adoption of structural adjustment programmes (SAP) by SSA countries in the mid-1980s and the abatement of the Cold War at the end of the decade, new anxieties have emerged to challenge established assumptions, analysis and praxis. The last decade has seen a phenomenal proliferation of armed intra-state conflicts, which have not only shaped Africa's foreign relations, but also featured on the foreign policy agenda of its states and regional organisations. This trend contradicts old assumptions in which the foreign policies of SSA states were explained exclusively within the contexts of colonialism, the Cold War and its aftermath, debt and structural adjustment.